Tracking Global Progress and Issues of Sustainable Development Goals - Sharma, Gyanendra Raj; Sharma, Surendra Raj; Timsina, Tirtha Raj (Teacher Half-Yearly Journal, 2025)
The Sustainable Development Goals (SDGs) are a global agenda adopted by 193 countries under the 2030 Agenda for Sustainable Development, aiming for economic prosperity, social advancement, environmental restoration, and better governance. Sustainable development is crucial for the survival and well-being of individuals, societies, and the planet, offering all peace, prosperity, and safety. This study examines the SDGs and their indicators targeted at global progress. This paper's main aim and objectives are to provide a clear understanding of the rationale of SDGs in addressing urgent global issues as a shared effort of the global community under the leadership of the United Nations. The article focuses on SDG goals, targets, and indicators associated with progress up to mid-point 2023. A careful examination of these measurement systems assesses the status of international sustainability initiatives with attention to both areas of excellent performance and long-term inadequacies requiring immediate global attention. Drawing from a wide range of data sources and published reports, this exploration offers a comprehensive overview of successes and failures in the worldwide effort to realize the SDGs. These findings give stakeholders, policymakers, and academics crucial information to guide a more direct path to achieving the SDGs.